Colorectal robotic surgery: INCA's experience - Valadão,Marcus (2019)
ABSTRACT Introduction: Minimally invasive surgery has revolutionized surgical management in the treatment of colorectal neoplasms, reducing morbidity and mortality, hospitalization, inactivity time and minimizing cost, as well as providing adequate oncological results when compared to the conventional approach. Robotic surgery, with Da Vinci Platform, emerges as a step ahead for its potentials. The objective of this article is to report the single institutional experience with the use of Da Vinci Platform in robotic colorectal surgeries performed at a reference center in oncological surgery in Brazil. Materials and methods: A retrospective cohort study was conducted based on the prospective database of patients from the institution submitted to robotic surgery for treatment of colorectal cancer from July 2012 to September 2017. Clinical and surgical variables were analyzed as predictors of morbidity and mortality. Results: A total of 117 patients underwent robotic surgery. The complications related to surgery occurred in 33 patients (28%), the most frequent being anastomotic fistula and surgical wound infection, which corresponded to 11% and 3%, respectively. Conversion rate was 1.7%. Median length of stay was 5 days. The only variable associated with increase of complications and death risk was BMI >30, with p-value of 0.038 and 0.027, respectively. Conclusion: Robotic surgery is safe and feasible for approaching colorectal cancer surgeries, presenting satisfactory results regarding length of hospital stay and rate of operative complications, as well as presenting a low rate of conversion. Obesity has been shown to be a risk factor for surgical complication in robotic colorectal surgery.